Pelaksanaan Supervisi Terhadap Kinerja Guru Dalam Proses Pembelajaran di SMP N 2 Kayuagung - Ibrahim, Ibrahim; Astuti, Mardiah; Reno, Ahmad (Faidatuna, 2023)
This research is entitled "Implementation of Supervision of Teacher Performance in the Learning Process at SMP N 2 Kayuagung". This research is to see how the implementation of supervision of teacher performance in the learning process, as well as the supporting factors and inhibiting factors in the implementation of supervision of teacher performance in the learning process at SMP Negeri 3 Kayuagung. This type of research is field research with a qualitative descriptive approach, with data collection techniques through observation, interviews and documentation. While data analysis uses an interactive model, namely data reduction, data presentation and data verification. The results of this study are the implementation of Supervision of Teacher Performance in the Learning Process at SMP N 2 Kayuagung, which is carried out by the school principal. Supervision has been running well and routinely carried out every year. The implementation stages consist of activities before the supervision process, supervision implementation activities and activities after supervision. Teacher performance in the learning process consists of three teaching and learning process activities, namely activities before the teaching and learning process, teaching and learning process activities, activities after the teaching and learning process. The teacher's performance in the learning process can be said to be good, although there are still obstacles encountered in the learning process by some teachers in carrying out their duties not in accordance with the criteria of a professional teacher.